The Clique Numbers and Chromatic Numbers of The Coprime Graph of a Dihedral Group. Issue 1 (March 2021) - Syarifudin, A G; Wardhana, I G A W; Switrayni, N W; Aini, Q
Abstract: The graph has many properties and characterizations. One interesting topic to discuss is the clique numbers and chromatic numbers. This research will determine the clique numbers and chromatic numbers of the coprime graph of the dihedral group. One of the main results is if n = 2 k then the chromatics numbers of the coprime graph of the dihedral group are 2, and if n is odd composite numbers, then the clique numbers and chromatics numbers are (m + 2).